A Study into the Barriers of Value Management Implementation in Public Sector Sarawak - Tay, Esther Sze May (2015)
Value Management is a philosophy and set of techniques that used as guidelines to fulfill the client’s needs at the lowest life cycle project cost while maintaining the required value, function and quality of the project. It has been widely accepted internationally and is now being used in the Malaysian construction industry. However, the application of Value Management in Malaysian construction industry is still low, especially in Sarawak. This paper provides a brief review of the historical development of and approaches to Value Management, as practiced internationally and in Malaysia. A further study has been carried out to determine the barriers of implementing Value Management in public sector of Sarawak by using online questionnaire. The paper concludes by discussing the main barriers and recommending the possible solutions for this issue.